Racism : a very short introduction - Rattansi, Ali. (New York : Oxford University Press, 2007)
Offers a brief introduction to racism that describes racial issues throughout history, science, politics, and popular culture; and also discusses the Holocaust, disadvantages of African-Americans, racism and sexuality, "Islamophobia," and other related topics.
Includes bibliographical references (p. 175-181) and index.
Adult
Keywords: Racism; Racism